Kinetics of the Water Release of Hygroscopic Acrylamide Gel Embedded in Calcium Chloride ‎by Thermogravimetric Analysis (Global Journal of Science Frontier Research, 2023)
Poly acrylamide gel was synthesized by radical polymerization of acrylamide and N N - methylene-bisacrylamide in the presence of benzoyl peroxide and carbon nanotubes The dry product was saturated with calcium chloride and prepared for water absorption and desorption The kinetics of water desorption of poly acrylamide gel embedded with hygroscopic calcium chloride DHG was studied from thermograms data of thermogravimetric analysis TGA DHG captures vapor from the environment and releases it as fresh water it can be used as the condenser to build atmospheric water generators AWGs to alleviate the freshwater stress rusting from innovative activities such as industrial agricultural rural and defense endeavors The kinetics parameters of the synthesized DHG showed that it absorbed environmental vapor at room temperature and released water below its boiling point 40 to 90 C temperatures achievable under sunlight via the photothermal effect In this work the energy barrier of DHG to release water Ea was evaluated from thermogravimetric measurements using the isoconversional method The values of Ea varied with temperature it was highest at t 40 C and became negligible and negative at t 50 C indicating that the water release was not required extra energy The water release rate was increasing with temperature showing a maximum rate around 75-89 C
Keywords: steam harvesting; dew collection; freshwater; desiccants; thermoresponsive